2020
DOI: 10.1364/oe.397636
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric carrier assisted differential detection receiver with low-complexity signal-signal beating interference mitigation

Abstract: Low-cost, spectrally efficient self-coherent detection capable of optical field recovery is desired for inter-data center connections and metro networks. In this work, a simplified symmetric carrier assisted differential detection (S-CADD) receiver structure is proposed, which removes the single-ended photodiode branch and saves one ADC in standard asymmetric CADD (A-CADD) receivers. To compensate for the signal-signal beating (SSBI) impairment, a low-complexity iterative SSBI mitigation algorithm is put forwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Generally, after the square law detection of PD for the input signals, as shown in our system, the signal-to-signal beat interference (SSBI) occupies the same bandwidth as the signal from zero frequency. However, in our experiments, due to the wide guard band and high input carrier-to-signal power ratio (CSPR, ~12 dB), the influence of the SSBI on the system is marginal [32]- [34].…”
Section: Discussionmentioning
confidence: 75%
“…Generally, after the square law detection of PD for the input signals, as shown in our system, the signal-to-signal beat interference (SSBI) occupies the same bandwidth as the signal from zero frequency. However, in our experiments, due to the wide guard band and high input carrier-to-signal power ratio (CSPR, ~12 dB), the influence of the SSBI on the system is marginal [32]- [34].…”
Section: Discussionmentioning
confidence: 75%
“…In Ref. [19], the theoretical derivation of the complexvalued optical DSB transmission with CADD receiver has been given, but the laser phase noise and fiber chromatic dispersion were neglected. It has been demonstrated that the EEPN originates from the interaction of laser phase noise and fiber chromatic dispersion [21][22][23][24][25][26].…”
Section: System Model and Pda-bps Algorithmmentioning
confidence: 99%
“…And the Rx.DSP includes the SSBI cancellation, inverse transfer function, EDC, down-conversion, matched RRC filter, synchronization, equalization, PDA-BPS algorithm, symbol decision, and finally the SNR estimation module. The SSBI cancellation includes SSBI complex iterative elimination algorithm and SSBI simplified iterative elimination algorithm [19].…”
Section: A Simulation Setupmentioning
confidence: 99%
See 2 more Smart Citations